Organic photovoltaics incorporating fulleroisoquinolinones as n-type materials - Chen, Chih-Ping; Luo, Charlene; Ting, Ching; Chuang, Shih-Ching (Chemical communications (Cambridge, England), 2011)
Fulleroisoquinolinones have been synthesized by palladium-catalyzed annulation of N-alkyl benzamides with C-60. A device incorporating fulleroisoquinolinones and the conjugated polymer P3HT exhibited power conversion efficiency up to 2.3% under AM 1.5G irradiation.